Seronegative spondyloarthritis and Darier's disease: more than a casual association? - C. Cosso; F. Rongioletti; G. Zampogna; D. Camellino; M. Cutolo; M. A. Cimmino (PAGEPress Publications, 2013)
A 46-year old man, affected by Darier's disease (DD), was seen because of right hand pain, later extended to shoulders and ankles. Physical examination showed swelling and tenderness of the wrist, metacarpophalangeal and metatarsophalangeal joints, of the right Achilles tendon's enthesis and of the left knee, with psoriatic-like lesions of the scalp. A diagnosis of seronegative spondyloarthritis, supported by HLA-B27 positivity and by the magnetic resonance imaging fi nding of hand synovitis and unilateral sacro-iliitis, was made. The correlation between DD, spondyloarthritis and psoriasis has been already anecdotally reported. Further observations may clarify if this association is more than casual.